عقد تخزين الخاليا الجذعية لإلنسان - م.م. كيفي مغديد قادر; د. تحسين حمد سمايل (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Our Research is about “Saving humanitarian stem cells contract” during our research we tried to focus on all the legal subjects which relate with the contract by: giving a definition to the contract &explaining all theessential elements of it. After that, we tried to give a legal qualificationto the contract byregardingit as one of the practical example of the construction and Holding deposit contract. After that, we tried to make a discrimination between the contract& all other similar contracts by showing all the similarities and contrast points between themsuch as: the labor contract, agency contract and rent contract.After that, we did explain all the elements of the contract which are: agreement of both of both sides of the contract -the baldbank and the customer- the placeand the reason which stands behind the contract. With the fourth element which is the deliverance of the customer’s stem cells to the bald bank. Then we did explain all the bilateral obligations which can be imposed on the two parts of the contract such as: purification, Storing and saving the customer’s stem cells for specific time and the customer’s obligations such as: paying the fee& Storage charges to the blood bank. We finished our research by showing all the &recommendations which we could obtain it on the saving of the humanitarian stem cells contract.